(untitled) (Eurasian Scientific Herald, 2022)
The article describes the role of genres in explaining the essence of the literature of the national renaissance, as well as the stage of formation of the novel genre from these genres. The emergence of the novel genre in Uzbek literature and the first attempts in this genre, as well as comments on the successes and failures of these works